Kinesthetic-Audio Methods in Teaching Islamic Education to Visually Impaired Students at Nagan Raya Special School, Aceh - Khairuddin Hasan; Dira Nita Yulia Putri; Mohd Lokman Bin Marzuki (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
The study aims to describe the use of kinesthetic and audio methods in Islamic education learning for blind children. Another objective is to determine the combination of the role of teachers as motivators, facilitators and evaluators in implementing these methods. The research approach used was qualitative with a case study method. Determination of sources was conducted using purposive sampling techniques. Data collection techniques were carried out through interviews, observations, and documentation studies. Data credibility testing was conducted using source triangulation, theoretical validity, independent analysis, and member checking. Data analysis was carried out by organizing the data, creating categories, determining themes and patterns, and seeking alternative explanations of the data. The results of the study indicate that the application of kinesthetic and audio methods uses five techniques, namely direct approach, repetition, practice breaks, turn rotation and memorization reinforcement. These techniques are applied adaptively depending on the psychological condition of students. The completeness of learning tools for children with special needs supports the application of kinesthetic-audio methods. Islamic education teachers play a role as motivators, facilitators and evaluators systematically and deliberatively. These three roles are combined to minimize learning barriers for blind children. Evaluation using the kinesthetic-audio method does not make students a single object in a repressive manner, but rather as a diagnostic process for aspects of teacher competence, method accuracy, and implementation of learning procedures.